Antibacterial Compounds from Red Seaweeds (Rhodophyta) - Noer Kasanah; Triyanto Triyanto; Drajad Sarwo Seto; Windi Amelia; Alim Isnansetyo (Indonesian Journal of Chemistry, 2015)
Seaweeds produce great variety of metabolites benefit for human. Red seaweeds (Rhodophyta) are well known as producer of phycocolloids such agar, agarose, carragenan and great variety of secondary metabolites. This review discusses the red algal secondary metabolites with antibacterial activity. The chemical constituents of red algae are steroid, terpenoid, acetogenin and dominated by halogenated compounds mainly brominated compounds. Novel compounds with intriguing skeleton are also reported such as bromophycolides and neurymenolides. In summary, red seaweeds are potential sources for antibacterial agents and can serve as lead in synthesis of new natural medicines.